2019
DOI: 10.1590/0104-6632.20190361s20170458
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Precipitated Silica From Palm Oil Mill Fly Ash Using Co2 Impregnation and Mechanical Fragmentation

Abstract: In this research, sol-gel precipitation using CO 2 impregnation and mechanical fragmentation method was applied to produce precipitated silica from Palm Oil Mill Fly Ash (POMFA). Carbon dioxide (CO 2) was used in order to reduce the cost of the process and to enable sodium hydroxide recovery. The precipitation process was done in a stirred temperature-controlled baffled glass precipitator. The response surface method with the central composite design was applied to optimize the stirring speed and the CO 2 flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The XRD analysis results showed in graph Figure 2 indicated that the silica precipitated sample was dominated by the amorphous phase with the broadening of the peak centered at a 2Ɵ between 20-30°. This phase had the same type as silica precipitates that had been produced from natural materials of quartz sand in previous studies [6] as well as from bio resources like palm oil mill fly ash [22].…”
Section: Characterization Of Silica Precipitate As Raw Materials For ...mentioning
confidence: 90%
“…The XRD analysis results showed in graph Figure 2 indicated that the silica precipitated sample was dominated by the amorphous phase with the broadening of the peak centered at a 2Ɵ between 20-30°. This phase had the same type as silica precipitates that had been produced from natural materials of quartz sand in previous studies [6] as well as from bio resources like palm oil mill fly ash [22].…”
Section: Characterization Of Silica Precipitate As Raw Materials For ...mentioning
confidence: 90%
“…Though, this process is not a suitable means for modification carried out in the aqueous medium. Significantly, if organic molecules are involved as it will dissolve in the dissolution process [125]. Impregnating silica into the cellulose aerogel can generate material with better thermal stability and high hydrophobicity properties than unmodified cellulose aerogel alone [126].…”
Section: Impregnation Methodsmentioning
confidence: 99%
“…The solution was further filtered to obtain silica gel and washed with hot distilled water to remove impurities. Finally, the silica gel was dried at 80 °C for 4 h ( Figure 1 ) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%